Prognostic role of nutrition parameters on short- and long-term outcome in patients with primary resectable pancreatic ductal adenocarcinoma - Bareiß, Sophie; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Clinical Nutrition ESPEN, 2024)
Purpose: Nutrition status of patients with pancreatic ductal adenocarcinoma (PDAC) has gained an increasing importance - especially in the preoperative setting. The aim of the present study was to evaluate different preoperative nutritional parameters including body composition parameters regarding their impact on short- and long-term outcome in patients with resectable PDAC. Methods: This retrospective single center study included 162 patients, who underwent primary resection of PDAC from January 2003 to December 2018 at the University Hospital of Erlangen. The influence of different preoperative nutrition parameters as well as different CT-based body composition parameters on short- (major morbidity, postoperative pancreatic fistula (POPF) and longer hospital stay) as well as on long-term outcome (overall and disease-free survival) were tested using multiple regression analysis. Results: Major morbidity and POPF occurred in 30% respectively 18%. Median length of hospital stay was 18 days. Median overall and disease free survival were 20.3 respectively 12.0 months. Multivariate analysis revealed among the different nutritional parameters following independent predictors: PMTH (psoas muscle thickness/height) for major morbidity (HR 2.1, p = 0.038), PMA (psoas muscle area) for a prolonged hospital stay >18 days (HR 7.3, p = 0.010) and NRS (nutritional risk score) for overall survival (HR 1.7, p = 0.043). Conclusion: In our cohort, nutritional parameters played a minor role in predicting short- and long-term outcome in patients with primary resectable PDAC, as there were only significant associations between selected psoas muscle parameters and short-term outcome parameters and the nutritional risk score (NRS) with the overall survival.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Body composition; Nutrition; Outcome; Pancreatic ductal adenocarcinoma; Primary resection; Survival